Música, materialidade e relações de gênero: categorias transbordantes - Talitha Couto Moreira (2012)
This work focuses on revisiting a selection of studies in ethnomusicology and sociology of musical education, conducted nationwide, dealing with intersections between music and gender in different ethnographic contexts, from a theoretical framework that involves gender theories as well as theories about music. Gender studies, after many years of accumulation in debates, have brought perspectives about the relativization of key categories involved in this reflection, such as gender, sexuality, and the very category of "gender". Studies involving the theme music also point to a destabilization of concepts for an overflow of boundaries with regard to fundamental structuring dualisms of Western ways of thinking, such as nature / culture, human / machine, natural / supernatural, human / animal and ideal / material. A power to trigger transformations in a material level in beings is related to music in this theoretical context, and music is also understood as belonging to an instance more material than ideal or metaphysical. The incorporation of gender debates in the revisited studies showed the potential to enrich the understanding of gender as well as music. Also the incorporation of theories concerning music presented, showed the potential to enrich, extend discussions of gender, as well as the very concept of music, present in various ethnographic contexts, in this case the indigenous people Wauja, in the Upper Xingu, studied by Maria Ines Cruz Mello, the context of young people in an urban school in Porto Alegre (RS), studied by Helena Lopes Silva, and the juremeiras of Xamba Nation (Olinda, PE), studied by Laila Andresa Cavalcante Rosa. Will be discussed the concepts and reflections on the theme of music and gender present in the works revisited in order to establish connections between the realities of the contexts studied and theories brought about the intersection between music, gender and anthropology.